Pathological analysis of Afghanistan’s tax system in the light of tax principles - Ariyan Ghassemi; Alireza Mohseny (دانشنامه حقوق اقتصادی, 2025)
Today, financial law scholars consider taxes and tax policies to be extremely important and vital in a country's economy. Having a functional and successful tax system can steer a country towards development and minimize economic and social problems. This tax system is always subject to the macroeconomic policies of the ruling power, and the government resorts to a tool called law to enforce these policies.In this research, by collecting resources through library-internet methods and by analysis and description, Afghanistan's tax system has been examined from beginning to end in the laws and regulations of tax principles. However, the main question is: what challenges does Afghanistan's tax system face in light of tax principles as a criterion? On the other hand, if it is assumed that despite adhering to some tax principles, Afghanistan's tax system is still not transparent and accountable and cannot cover the enormous public expenses through taxes, it must be said that what causes problems in the collection and enforcement of tax regulations is the ambiguity and multiplicity of tax regulations. Furthermore, the lack of specialists and budget has prevented the government from creating an electronic system for tax calculations and banking. Therefore, precise oversight and control over tax collection methods do not occur, which leads to widespread tax evasion, collusion, non-payment, and concealment of income. These factors have led to the emergence of tax challenges and damages in the tax system. By creating an electronic system, precise and easy monitoring of tax collection and enforcement, raising public awareness of tax matters, preventing tax evasion, and increasing customs tariffs on imported products, the desired outcome of the tax system can be achieved.